First clinical and myopathological description of a myofibrillar myopathy with congenital onset and homozygous mutation in FLNC. Issue 9 (11th July 2020) - Kölbel, Heike; Roos, Andreas; van der Ven, Peter F. M.; Evangelista, Teresinha; Nolte, Kay; Johnson, Katherine; Töpf, Ana; Wilson, Michael; Kress, Wolfram; Sickmann, Albert; Straub, Volker; Kollipara, Laxmikanth; et al.
Abstract: Filamin C (encoded by the FLNC gene) is a large actin‐cross‐linking protein involved in shaping the actin cytoskeleton in response to signaling events both at the sarcolemma and at myofibrillar Z‐discs of cross‐striated muscle cells. Multiple mutations in FLNC are associated with myofibrillar myopathies of autosomal‐dominant inheritance. Here, we describe for the first time a boy with congenital onset of generalized muscular hypotonia and muscular weakness, delayed motor development but no cardiac involvement associated with a homozygous FLNC mutation c.1325C>G (p.Pro442Arg). We performed ultramorphological, proteomic, and functional investigations as well as immunological studies of known marker proteins for dominant filaminopathies. We show that the mutant protein is expressed in similar quantities as the wild‐type variant in control skeletal muscle fibers. The proteomic signature of quadriceps muscle is altered and ultrastructural perturbations are evident. Moreover, filaminopathy marker proteins are comparable both in our homozygous and a dominant control case (c.5161delG). Biochemical investigations demonstrate that the recombinant mutant protein is less stable and more prone to degradation by proteolytic enzymes than the wild‐type variant. The unusual congenital presentation of the disease clearly demonstrates that homozygosity for mutations in FLNC severely aggravates the phenotype.